Insight in substance use disorder: A systematic review of the literature. (December 2020) - Raftery, Dayle; Kelly, Peter J.; Deane, Frank P.; Baker, Amanda L.; Ingram, Isabella; Goh, Melvin C.W.; Lubman, Dan I.; Carter, Greg; Turner, Alyna; Dean, Olivia M.; Sinclair, Barbara L.; McKetin, Rebecca
Highlights: Systematic review of five databases resulted in 20 articles that met criteria. There were 13 measures of insight used, with only one designed for use within SUD. A wide range of insight conceptualizations muddies the picture of insight in SUD. Insight may have implications for SUD treatment adherence and outcomes. Abstract: Insight refers to a person's understanding of themselves and the world around them. Recent literature has explored people's insight into their substance use disorder (SUD) and how this is linked to treatment adherence, abstinence rates, and comorbid mental health symptoms. The aim of this systematic review was to synthesise and critically examine the existing literature on insight in SUD. Five academic databases (Medline, PsychINFO, SCOPUS, CINAHL, Web of Science) were searched for key terms related to insight and substance use. Included studies were on humans aged 18 years or over with SUD that examined the relationship between substance use and insight using a quantifiable measure of insight. Of 10, 067 identified papers, 20 met the inclusion criteria, employing 13 different measures of insight. The most commonly used measure was the Hanil Alcohol Insight Scale (HAIS) which was the only measure designed for a substance use population and was specific to alcohol use. Based on a pooled sample from five studies (n = 585), 57% of participants had poor insight, 36% had fair insight, and 7% had good insight on the HAIS. Better insight was generally related to negative consequences from substance use, better treatment adherence and maintaining abstinence. Insight appears to be an important factor to consider within SUD. Exploring the most appropriate way to measure insight and assess its role in SUD has implications for intervention design, and engaging and maintaining people with SUD in treatment.